2019
DOI: 10.3762/bjnano.10.84
|View full text |Cite
|
Sign up to set email alerts
|

Novel reversibly switchable wettability of superhydrophobic–superhydrophilic surfaces induced by charge injection and heating

Abstract: Reversibly switching wettability between superhydrophobicity and superhydrophilicity has attracted widespread interest because of its important applications. In this work, we propose a reversible superhydrophobic–superhydrophilic conversion induced by charge injection and heating. Different from the conventional electrowetting phenomenon caused by the accumulation of solid–liquid interfacial charges, we discovered a phenomenon where charge injection and accumulation at the solid surface results in a sharp incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Studies have found some common environmentally responsive superhydrophobic surfaces, such as light response, temperature response, pH response, electric field response, ionic liquid response, and magnetic response. Nowadays, a lot of waste oil and water mixtures are produced in the industrial production process, and superhydrophobic materials can not only separate these mixtures through filtration or single-phase selective absorption, but also realize the free switching of oil–water separation according to production needs in different external environments, which shows their strong industrial application value. Therefore, the preparation of intelligent responsive materials has become an important issue of industrial production. However, due to the high cost and complex preparation process, their application value in industrial production is limited to a certain extent. , After experimental research and practical verification, it is gradually found that temperature-responsive superhydrophobic surfaces have the advantages of a fast response, low requirement of preparation equipment, and simple preparation process, which make them show a greater production and application value and also set off an upsurge of academic research on temperature-responsive superhydrophobic surfaces. , …”
Section: Introductionmentioning
confidence: 99%
“…Studies have found some common environmentally responsive superhydrophobic surfaces, such as light response, temperature response, pH response, electric field response, ionic liquid response, and magnetic response. Nowadays, a lot of waste oil and water mixtures are produced in the industrial production process, and superhydrophobic materials can not only separate these mixtures through filtration or single-phase selective absorption, but also realize the free switching of oil–water separation according to production needs in different external environments, which shows their strong industrial application value. Therefore, the preparation of intelligent responsive materials has become an important issue of industrial production. However, due to the high cost and complex preparation process, their application value in industrial production is limited to a certain extent. , After experimental research and practical verification, it is gradually found that temperature-responsive superhydrophobic surfaces have the advantages of a fast response, low requirement of preparation equipment, and simple preparation process, which make them show a greater production and application value and also set off an upsurge of academic research on temperature-responsive superhydrophobic surfaces. , …”
Section: Introductionmentioning
confidence: 99%